Importance of Table of Specification in Validating the Summative Evaluation of Students. - Ghulam Mustafa Rajput, Muhammad /Oaf Rao, Husan Barra Channar, Altaf Khan , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To assess the importance, benefits and utilization of the table of specification. Methods: This review study was conducted in the Begum Bilques Sultana Institute of Nursing, Peoples University of Medical & Health Sciences Shaheed Benazir Abad from 25th December, 2015 to 5th February, 2016. A systematic search was carried out to identify the articles providing the understanding, importance, validity and utilization of table of specification. Two reviews were made for the assessment of data, while the third review was made for the settlement of the final consensus. A narrative approach was applied to synthesize the reviews. Results: Total 215 potential articles were assessed .All the articles were scrutinized according to the pre-established inclusion and exclusion criteria. Out of which 24 articles were identified meeting the inclusion criteria. Two reviews were made for the assessment of data, while the third review was made for final consensus. Conclusion: Authentic and valid evaluation score is possible with the proper construction of the table of specification. The core consideration to construct the table of specification includes the selection of proper content to be taught, time spent for the content, percent of class time on topic, number of test items, recognizing the levels of cognitive ,psychomotor and affective domains for the construction of test items.